Optimal Taxation, Child Care and Models of the Household - Patricia Apps; Ray Rees (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper presents the properties of optimal piecewise linear tax systems for two-earner households, based on joint and individual incomes respectively. A key contribution is the analysis of the interaction between second earner wage differences, variation in the price of child care and domestic productivity differences as determinants of across-household heterogeneity in second earner labour supply, and of the resulting relationship between household income and the wellbeing of household members. A central result is that taking account of a richer and more realistic specification of household time use widens the set of cases in which individual taxation is welfare-superior.
Keywords: H21; J22; H31; H24; 330; optimal taxation; labour supply; time use; child care; household production; inequality